Blood concentrations of B-type natriuretic peptide and N-terminal prohormone B-type natriuretic peptide as markers of left ventricle diastolic function in patients with chronic renal failure - Petrović, Milica; Grdinić, Aleksandra; Bokonjić, Dubravko; Rabrenović, Violeta; Antić, Svetlana; Terzić, Brankica; Stamenković, Dušica; Stajić, Zoran; Petrović, Dejan; Ignjatović, Ljiljana; Pejović, Janko; Jovanović, Dragan (Vojnosanitetski pregled, 2017)
Background/Aim. Patients with chronic renal failure (CRF) have increased cardiovascular morbidity and mortality. It is unknown which biomarkers best describe the degree of diastolic dysfunction in patients with CRF. The aim of this study was to determine the correlation between B-type natriuretic peptide (BNP), N-terminal prohormone brain natriuretic peptide (NTproBNP) and left ventricular diastolic dysfunction (DD-LV) with the degree of CRF. Methods. The study included 100 adult patients with CRF without major cardiac and cerebral incidents who did not start actively treating CRF. According to the degree of CRF, the patients were divided into two groups: G1 (moderate degree), glomerular filtration rate (GFR) ≥ 30 mL/min/1.73 m2, and G2 (more severe degree), GFR
Keywords: kidney failure; chronic; glomerular filtration rate; ventricular function; left; natriuretic peptides; biological markers; sensitivity and specificity